Weak Darboux property and transitivity of linear mappings on topological vector spaces - Maslyuchenko, V.K.; Nesterenko, V.V. (Carpathian Mathematical Publications, 2013)
It is shown that every linear mapping on topological vector spaces always has weak Darboux property, therefore, it is continuous if and only if it is transitive. For finite-dimensional mapping f with values in Hausdorff topological vector space the following conditions are equivalent: (i) f is continuous; (ii) graph of f is closed; (iii) kernel of f is closed; (iv) f is transition map.